Corrosion-resistant and high-weather-resistant alloy resin tile and preparation process thereof
By using a combination of bio-based polymer materials and dynamic cross-linking technology in traditional resin tiles, combined with multi-layer co-extrusion molding process and intelligent monitoring modules, alloy resin tiles with high weather resistance, corrosion resistance and intelligence functions have been developed. It solves the weather resistance and corrosion resistance of traditional tiles in harsh environments, and achieves the goal of multifunctional and environmental protection.
Patent Information
- Application Number
- CN202411890690.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Traditional resin tiles have insufficient weather resistance, limited anti-corrosion performance and single functions in harsh environments such as high ultraviolet radiation, high humidity, and high salt spray, which are difficult to meet the long-term stability and multifunctional needs of modern buildings.
The compound enhancement of the bio-based polymer material polyethylene furandiformate and modified potassium titanate whiskers is used, combined with dynamic crosslinking technology, multi-layer coextrusion molding process and intelligent monitoring module, developed high weather resistance, Alloy resin tiles with anticorrosion, intelligence and environmental protection characteristics.
It significantly improves the weather resistance and corrosion resistance of the shingles, extends the service life, realizes self-cleaning and photocatalytic degradation functions, and realizes real-time perception of crack detection and aging status through intelligent monitoring modules, reducing maintenance costs.
Smart Images

Figure CN119427878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an anti-corrosion and highly weather-resistant alloy resin tile and a preparation process thereof. Background Art
[0002] In recent years, with the rapid development of the modern construction industry, roofing materials, as an important part of building structures, have increasingly higher performance and functional requirements. Traditional resin tiles used in conventional environments, such as polyvinyl chloride (PVC) tiles, polycarbonate (PC) tiles, and acrylonitrile-styrene-acrylate (ASA) tiles, have become the mainstream choice due to their good mechanical properties and cost advantages. However, with the variability of the global climate and the increase in extreme environments, traditional resin tiles have gradually exposed the defects of insufficient weather resistance, limited anti-corrosion performance, and single function, and cannot meet the long-term stability requirements of modern buildings under harsh conditions such as high ultraviolet radiation, high humidity, and high salt spray.
[0003] In terms of weather resistance, traditional resin tiles usually use petrochemical-based materials, which are prone to aging under long-term ultraviolet radiation, such as fading, cracking, and degradation of surface properties. Especially in tropical or plateau areas with strong ultraviolet rays, the life of traditional tiles will be significantly shortened, and it is difficult to maintain long-term structural and aesthetic stability. Although some modified materials enhance weather resistance by adding ultraviolet absorbers or antioxidants, their effects are limited, especially for building tiles exposed to sunlight for a long time. Such modification solutions are difficult to provide comprehensive and lasting protection.
[0004] In terms of corrosion resistance, building roofing materials are exposed to the natural environment for a long time and are susceptible to corrosion from acid rain, salt spray and moisture. Traditional resin tiles have weak resistance to these factors, especially in coastal areas or areas with severe industrial pollution, where salt spray and corrosive gases will accelerate the performance degradation of tiles. This problem not only affects the appearance and service life of the building, but may also cause more serious structural safety problems. In the prior art, the corrosion resistance of materials is usually improved by coating a corrosion-resistant layer or adding fillers, but these measures are mostly passive protection, and it is difficult to achieve essential corrosion resistance improvements on the material itself, while the processing cost and complexity are also significantly increased.
[0005] In addition, the functions of traditional resin tiles are relatively simple, usually only having basic functions such as sunshade and rain protection, which makes it difficult to adapt to the needs of modern buildings for multifunctional materials. For example, in terms of self-cleaning, dust and pollutants are easily accumulated on the surface of traditional tiles, requiring frequent cleaning and maintenance; in terms of intelligent applications, existing resin tiles have not yet been able to achieve real-time perception and monitoring of their own structural status, such as crack expansion and aging status, and cannot provide users with timely alarms and maintenance suggestions, thereby increasing the maintenance cost and management complexity of buildings.
[0006] As the demand for green and environmentally friendly materials in the construction industry grows, traditional resin tiles have been questioned for using petrochemical-based materials. These materials not only cause resource waste and carbon emissions during the production process, but their non-degradability after the end of their service life also brings serious environmental pollution problems. Although the research on bio-based materials has gradually gained attention, their application in the field of roof tiles is still relatively limited. Existing attempts are mainly focused on basic material substitution, and have not yet been able to combine the advantages of bio-based materials to develop high-performance and multifunctional tiles.
[0007] In terms of processing technology, the manufacturing process of traditional resin tiles mainly relies on the extrusion molding technology of a single layer of material. Although it has certain production efficiency, it is insufficient in terms of multi-layer structure integration and complex function realization. Some multifunctional tiles attempt to achieve specific functions through multiple processing or coating technologies, but the process is complicated and the cost is high. At the same time, the interlayer bonding force is weak, and it is easy to cause functional failure due to peeling or crack expansion. In addition, the surface treatment of tiles in the existing technology mostly adopts spraying or coating, and its durability and functional stability are far inferior to modern processes.
[0008] Therefore, how to provide a corrosion-resistant and highly weather-resistant alloy resin tile and a preparation process thereof is a problem that technical personnel in this field urgently need to solve. Summary of the invention
[0009] One purpose of the present invention is to propose an anti-corrosion and highly weather-resistant alloy resin tile and its preparation process. The present invention combines bio-based polymer materials, dynamic cross-linking technology, multi-layer co-extrusion molding process and intelligent monitoring module to develop an anti-corrosion and highly weather-resistant alloy resin tile. The weather resistance and anti-corrosion performance of the tile material are significantly improved through the composite reinforcement of polyethylene furandicarboxylate and modified potassium titanate whiskers; the ultraviolet shielding and photocatalytic functions are achieved by using vanadium oxide and zinc oxide nanoparticles; the introduction of fluorinated graphene coating provides super-hydrophobic self-cleaning ability; the intelligent monitoring module realizes crack detection and aging prediction, and has excellent durability, corrosion resistance, intelligence and environmental protection characteristics.
[0010] A process for preparing an anti-corrosion and highly weather-resistant alloy resin tile according to an embodiment of the present invention comprises the following steps: S1, mixing polyethylene furandicarboxylate with a toughening agent and an ultraviolet absorber, forming a matrix material by melt processing, and uniformly adding modified potassium titanate whiskers with fluorine-containing groups grafted on the surface into the matrix material by ultrasonic dispersion technology to prepare a basic composite material; S2. Adding vanadium oxide and zinc oxide composite nanoparticles prepared by a sol-gel method to the basic composite material, and performing surface modification on the composite nanoparticles to prepare a composite material with ultraviolet shielding and photocatalytic functions; S3. Introducing dynamically cross-linked fluorosilicone-based polymers into composite materials with UV shielding and photocatalytic functions, and preparing surface functional materials through dynamic cross-linking technology; S4, preparing and molding the surface functional material, the middle layer nanofiber reinforced composite material and the bottom layer conductive polythiophene-based composite material respectively, and realizing uniform mixing of multiple components and directional arrangement of molecular chains through a dynamic rotating twin-screw extruder to form a multi-layer structure substrate; S5. The surface layer, the middle layer and the bottom layer are co-extruded synchronously by three-die extrusion technology to prepare multi-layer co-extruded tiles; S6. Use ultrasonic activated bonding technology to enhance the interlayer bonding strength of multi-layer co-extruded tiles; S7, depositing a fluorinated graphene nanofilm on the surface of the multi-layer co-extruded tile material using plasma enhanced chemical vapor deposition technology to form a super hydrophobic functional layer; S8. Conduct UV photocatalytic function tests on multi-layer co-extruded tiles to verify the active oxygen generation ability of surface nanoparticles, and complete crack detection and real-time perception of aging status through the conductive polythiophene composite layer embedded in the bottom layer combined with the intelligent monitoring module.
[0011] Optionally, the S3 specifically includes: S31, placing the prepared composite material with ultraviolet shielding and photocatalytic functions in a reactor, adding a dynamically cross-linked fluorosilicone-based polymer according to 15%-30% of the total mass of the composite material, starting the stirring device of the reactor, raising the temperature to 140° C., controlling the stirring speed to 200 rpm, and maintaining the stirring time for 30 minutes; S32, adding an initiator and an inhibitor during the mixing process, wherein the initiator is benzoyl peroxide, and the amount used is 0.2% of the total mass of the composite material; the inhibitor is hydroquinone, and the amount used is 0.1% of the total mass of the composite material, and continuously stirring to allow the fluorosilicone-based polymer to undergo a preliminary cross-linking reaction; S33, connect the dynamic stress loading device to the reactor, and apply shear rate through the device and shear stress , and set the dynamic stress frequency to 15 Hz, and continue the action for 2 hours to promote the formation of a cross-linked network of fluorosilicone-based polymers; S34, Real-time detection of dynamic mechanical properties of composite materials during dynamic crosslinking, monitoring of storage modulus and loss modulus , calculate the loss factor , control the loss factor range to 0.2-0.4; S35, after the dynamic cross-linking reaction is completed, the cross-linked composite material is slowly cooled to room temperature, and the cooled material is calendered using a calendering device to control the calendering thickness to be 50-80 microns; S36. Conduct surface roughness test on the sheet to ensure that the roughness is less than 0.2 microns. Perform dynamic thermomechanical analysis to test the storage modulus and weather resistance of the material, and conduct UV aging experiments to verify the UV shielding and photocatalytic stability of the surface functional material, and finally obtain the surface functional material.
[0012] Optionally, the S4 specifically includes: S41, placing the obtained surface functional material in an extruder to prepare a surface functional material, setting the temperature to 180°C-200°C, and setting the screw speed to 60rpm-80rpm, so that the material is fully plasticized and extruded into a uniform sheet, and the thickness is controlled to be 50-100 microns; S42, placing the nanofiber reinforced composite material in a twin-screw extruder to prepare an intermediate layer reinforcement material, adjusting the feed rate to 5-10 kg / h, setting the temperature to 200° C.-220° C., and the screw speed to 100 rpm-150 rpm, adding a continuous fiber reinforcement phase to form a shell-like layered structure, and forming a reinforcement material sheet with a thickness of 2 mm-3 mm by extrusion; S43, mixing the conductive polythiophene composite material and the flexible filler in a mass ratio of 9:1 and placing the mixture in a single screw extruder to prepare a bottom conductive material, setting the temperature to 160° C.-180° C. through a temperature control system, adjusting the screw speed to 50 rpm-70 rpm, and extruding the mixture into a sheet with a thickness of 100-150 μm by a thermoplastic molding process; S44, adding the surface layer functional material, the middle layer reinforcing material and the bottom layer conductive material into the dynamic rotating twin-screw extruder in sequence, adjusting the screw rotation speed to 100rpm-120rpm, setting the feeding order to the bottom layer material, the middle layer material and then the surface layer material, and controlling the temperature gradient to gradually increase from 180°C of the bottom layer to 220°C of the surface layer; S45, cooling the multilayer structure material extruded from the extruder through a cooling roller, setting the cooling roller temperature to 10°C-20°C, adjusting the inter-roller pressure to 1MPa-2MPa, and controlling the sheet thickness through a multi-stage roller cooling system; S46. Finally, a multilayer structure substrate is formed and the cooled multilayer structure material is subjected to a dynamic mechanical property test, and the bending modulus is greater than 80 MPa.
[0013] Optionally, the S8 specifically includes: S81. Place the multi-layer co-extruded tile material under a UV irradiation device, set the light intensity to 30mW / cm², the irradiation distance to 20cm, and the duration to 2 hours. Determine the active oxygen concentration generated on the tile surface by iodine titration. The active oxygen concentration generated is above; S82. Catalyze the tile surface under ultraviolet light for 1 hour, collect the degraded solution, and measure the transmittance change using an ultraviolet spectrophotometer: ; in, represents the degradation efficiency, represents the initial pollutant concentration, It indicates the concentration of pollutants after degradation; S83, applying a constant voltage to the conductive polythiophene composite layer at the bottom of the tile material , monitor the resistance value , when the resistance change rate exceeds 5%, it is marked as the crack occurrence point; S84, using the embedded intelligent monitoring module to record the resistance change trend of the conductive polythiophene composite layer in real time, the intelligent monitoring module sets an alarm mechanism, and records the aging crack growth curve; S85. Apply alternating stress to the tile surface to simulate the dynamic process of crack extension under environmental conditions. Set the alternating stress parameters to a frequency of 5 Hz and an amplitude of 2 MPa. Record the crack extension length after 2 hours of continuous stress to complete crack detection and real-time perception of aging status.
[0014] Optionally, the S84 specifically includes: S841. Based on the initial resistance of the conductive polythiophene composite layer, the relationship between the resistance change rate and the crack extension length during crack extension was measured experimentally to establish a dynamic crack extension model: ; in, represents the real-time resistance of the conductive polythiophene composite layer after crack expansion, represents the initial resistance of the conductive polythiophene composite layer, represents the sensitivity coefficient of crack extension, represents the nonlinear factor of crack growth, Indicates the crack extension length; S842, using a resistance sensor embedded in the bottom layer of the tile material, collecting resistance values and resistance change rates in real time at a sampling frequency of 100 times per second, and combining with timestamp records to form a time series data stream; S843, using support vector machine classification algorithm to perform multi-layer state classification of resistance change rate: ; in, represents the radial basis kernel function, Represents the feature vector Sample points, Represents the feature vector Sample points, represents the exponential function, represents the kernel width parameter; S844, based on Gaussian process regression and improved variational Bayesian inference, crack propagation prediction is performed, a Gaussian process model is established, and a resistance change curve is generated: ; in, represents the probability distribution of the resistance change rate, represents the crack extension length, represents the resistance change caused by crack extension, represents a normal distribution, represents the mean value of the resistance change rate corresponding to crack extension, represents the variance of the resistance change rate corresponding to crack extension; Improved variational Bayesian inference is used to optimize the update of crack extension posterior distribution: ; in, Indicates time The posterior distribution of crack extension length when Indicates time The predicted distribution of the resistance change rate when The crack length in time The prior distribution of ; Output the predicted value of future crack growth length and confidence interval ; S845. Combining the resistance change curve and the predicted crack extension length, the long short-term memory network is used to predict the trend of the crack aging state, and the aging crack extension curve is recorded; S846. According to the crack growth prediction results and trend analysis, the intelligent monitoring module sets three levels of alarm thresholds, including: Level 1 alarm, predicted crack growth in the next 5 hours ; Level 2 alarm, predicted crack growth in the next 3 hours ; Level 3 alarm, predicted crack extension value for the next hour .
[0015] According to an embodiment of the present invention, an anti-corrosion and highly weather-resistant alloy resin tile is composed of a surface functional layer, an intermediate layer and a bottom layer, specifically comprising: the surface functional layer is made of a dynamically cross-linked fluorine-silicon-based polymer, with a thickness of 50-100 microns, containing vanadium oxide and zinc oxide nanoparticles, and has ultraviolet shielding, self-cleaning and photocatalytic degradation functions; the surface is treated with a fluorinated graphene coating, has super-hydrophobic properties, and a water drop contact angle greater than 160°; The middle reinforcement layer is made of nanofiber reinforced composite material with a thickness of 2mm-3mm. It adopts a shell-like layered structure design and has high impact resistance and mechanical properties with a bending modulus greater than 80MPa. The bottom layer is made of a mixture of conductive polythiophene composite materials and flexible fillers, with a thickness of 100-150 microns. It has crack detection and aging status monitoring functions, and performs real-time data analysis and early warning through the embedded intelligent monitoring module; The surface layer, the middle layer and the bottom layer are bonded together by ultrasonic activated bonding technology and are integrally formed by a three-die co-extrusion process.
[0016] The beneficial effects of the present invention are: First, the present invention uses bio-based polymer materials based on polyethylene furandicarboxylate (PEF) to replace traditional petrochemical-based resins, achieving the renewability and environmental friendliness of the material source. PEF materials not only have excellent mechanical properties and chemical stability, but also greatly improve the weather resistance and corrosion resistance of tiles by combining with modified potassium titanate whiskers and composite nanoparticles. Compared with the rapid deterioration of traditional materials under ultraviolet radiation and extreme climatic conditions, the tiles of the present invention can still maintain more than 95% of color stability after 4,000 hours of ultraviolet aging test, significantly improving the service life and long-term reliability of the materials.
[0017] In addition, the present invention has developed a surface functional material with flexibility and self-healing ability by introducing dynamically cross-linked fluorosilicone-based polymers. The dynamic cross-linking technology forms a stable network structure on the surface of the tile material, which not only enhances the material's crack resistance, but also effectively inhibits the expansion of microcracks through a self-healing mechanism. In addition, the vanadium oxide and zinc oxide nanoparticles added to the surface material not only provide excellent UV shielding capabilities, but also give the tile surface a photocatalytic degradation function. Combined with the super-hydrophobic properties of the fluorinated graphene coating, the tile surface exhibits excellent self-cleaning performance, effectively avoiding the accumulation of dust, pollutants and biological attachment, and greatly reducing maintenance costs.
[0018] The middle layer is made of nanofiber reinforced composite materials, and the layered structure design imitating shells provides excellent impact resistance and toughness, significantly improving the mechanical properties of the tile. Compared with the defect of traditional tiles that are easily broken under wind load and physical impact, the tiles of the present invention have significantly improved bending modulus and impact strength, and can better cope with harsh natural conditions. The bottom conductive polythiophene composite material is combined with an embedded intelligent monitoring module to achieve real-time perception of crack detection and aging status. Through high-precision resistance sensors and improved variational Bayesian inference algorithms, the present invention can accurately predict the expansion trend of cracks and provide users with timely maintenance suggestions through a three-level alarm mechanism. This intelligent functional design fills the gap in the field of structural health monitoring of existing resin tiles and provides important guarantees for the long-term safety of buildings.
[0019] In terms of technology, the present invention adopts three-die co-extrusion technology to realize the synchronous molding of the surface layer, the middle layer and the bottom layer material, and enhances the bonding force of the multilayer structure by ultrasonic activation bonding technology. Compared with traditional multiple processing or spraying process, the process of the present invention is more efficient, while ensuring the consistency of material performance and the stability of interlayer bonding. The surface functional layer forms a super-hydrophobic coating by plasma enhanced chemical vapor deposition technology, and compared with traditional spraying technology, the coating prepared by the process is more uniform and the durability is significantly improved. In addition, the present invention does not use solvents in the whole process, avoids environmental pollution problems, and meets the concept of green manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 This is an overall flow chart of a preparation process of an anti-corrosion and highly weather-resistant alloy resin tile proposed by the present invention; Figure 2 This is a structural schematic diagram of a process for preparing corrosion-resistant and highly weather-resistant alloy resin tiles proposed by the present invention. DETAILED DESCRIPTION
[0021] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.
[0022] refer to Figure 1 A process for preparing corrosion-resistant and highly weather-resistant alloy resin tiles comprises the following steps: S1, mixing polyethylene furandicarboxylate with a toughening agent and an ultraviolet absorber, forming a matrix material by melt processing, and uniformly adding modified potassium titanate whiskers with fluorine-containing groups grafted on the surface into the matrix material by ultrasonic dispersion technology to prepare a basic composite material; S2. Adding vanadium oxide and zinc oxide composite nanoparticles prepared by a sol-gel method to the basic composite material, and performing surface modification on the composite nanoparticles to prepare a composite material with ultraviolet shielding and photocatalytic functions; S3. Introducing dynamically cross-linked fluorosilicone-based polymers into composite materials with UV shielding and photocatalytic functions, and preparing surface functional materials through dynamic cross-linking technology; S4, preparing and molding the surface functional material, the middle layer nanofiber reinforced composite material and the bottom layer conductive polythiophene-based composite material respectively, and realizing uniform mixing of multiple components and directional arrangement of molecular chains through a dynamic rotating twin-screw extruder to form a multi-layer structure substrate; S5. The surface layer, the middle layer and the bottom layer are co-extruded synchronously by three-die extrusion technology to prepare multi-layer co-extruded tiles; S6. Use ultrasonic activated bonding technology to enhance the interlayer bonding strength of multi-layer co-extruded tiles; S7, depositing a fluorinated graphene nanofilm on the surface of the multi-layer co-extruded tile material using plasma enhanced chemical vapor deposition technology to form a super hydrophobic functional layer; S8. Conduct UV photocatalytic function tests on multi-layer co-extruded tiles to verify the active oxygen generation ability of surface nanoparticles, and complete crack detection and real-time perception of aging status through the conductive polythiophene composite layer embedded in the bottom layer combined with the intelligent monitoring module.
[0023] In this implementation, S3 specifically includes: S31, placing the prepared composite material with ultraviolet shielding and photocatalytic functions in a reactor, adding a dynamically cross-linked fluorosilicone-based polymer according to 15%-30% of the total mass of the composite material, starting the stirring device of the reactor, raising the temperature to 140° C., controlling the stirring speed to 200 rpm, and maintaining the stirring time for 30 minutes; S32, adding an initiator and an inhibitor during the mixing process, wherein the initiator is benzoyl peroxide, and the amount used is 0.2% of the total mass of the composite material; the inhibitor is hydroquinone, and the amount used is 0.1% of the total mass of the composite material, and continuously stirring to allow the fluorosilicone-based polymer to undergo a preliminary cross-linking reaction; S33, connect the dynamic stress loading device to the reactor, and apply shear rate through the device and shear stress , and set the dynamic stress frequency to 15 Hz, and continue the action for 2 hours to promote the formation of a cross-linked network of fluorosilicone-based polymers; S34, Real-time detection of dynamic mechanical properties of composite materials during dynamic crosslinking, monitoring of storage modulus and loss modulus , calculate the loss factor , control the loss factor range to 0.2-0.4; S35, after the dynamic cross-linking reaction is completed, the cross-linked composite material is slowly cooled to room temperature, and the cooled material is calendered using a calendering device to control the calendering thickness to be 50-80 microns; S36. Conduct surface roughness test on the sheet to ensure that the roughness is less than 0.2 microns. Perform dynamic thermomechanical analysis to test the storage modulus and weather resistance of the material, and conduct UV aging experiments to verify the UV shielding and photocatalytic stability of the surface functional material, and finally obtain the surface functional material.
[0024] In this implementation manner, the S4 specifically includes: S41, placing the obtained surface functional material in an extruder to prepare a surface functional material, setting the temperature to 180°C-200°C, and setting the screw speed to 60rpm-80rpm, so that the material is fully plasticized and extruded into a uniform sheet, and the thickness is controlled to be 50-100 microns; S42, placing the nanofiber reinforced composite material in a twin-screw extruder to prepare an intermediate layer reinforcement material, adjusting the feed rate to 5-10 kg / h, setting the temperature to 200° C.-220° C., and the screw speed to 100 rpm-150 rpm, adding a continuous fiber reinforcement phase to form a shell-like layered structure, and forming a reinforcement material sheet with a thickness of 2 mm-3 mm by extrusion; S43, mixing the conductive polythiophene composite material and the flexible filler in a mass ratio of 9:1 and placing the mixture in a single screw extruder to prepare a bottom conductive material, setting the temperature to 160° C.-180° C. through a temperature control system, adjusting the screw speed to 50 rpm-70 rpm, and extruding the mixture into a sheet with a thickness of 100-150 μm by a thermoplastic molding process; S44, adding the surface layer functional material, the middle layer reinforcing material and the bottom layer conductive material into the dynamic rotating twin-screw extruder in sequence, adjusting the screw rotation speed to 100rpm-120rpm, setting the feeding order to the bottom layer material, the middle layer material and then the surface layer material, and controlling the temperature gradient to gradually increase from 180°C of the bottom layer to 220°C of the surface layer; S45, cooling the multilayer structure material extruded from the extruder through a cooling roller, setting the cooling roller temperature to 10°C-20°C, adjusting the inter-roller pressure to 1MPa-2MPa, and controlling the sheet thickness through a multi-stage roller cooling system; S46. Finally, a multilayer structure substrate is formed and the cooled multilayer structure material is subjected to a dynamic mechanical property test, and the bending modulus is greater than 80 MPa.
[0025] In this implementation manner, S8 specifically includes: S81. Place the multi-layer co-extruded tile material under a UV irradiation device, set the light intensity to 30mW / cm², the irradiation distance to 20cm, and the duration to 2 hours. Determine the active oxygen concentration generated on the tile surface by iodine titration. The active oxygen concentration generated is above; S82. Catalyze the tile surface under ultraviolet light for 1 hour, collect the degraded solution, and measure the transmittance change using an ultraviolet spectrophotometer: ; in, represents the degradation efficiency, represents the initial pollutant concentration, It indicates the concentration of pollutants after degradation; S83, applying a constant voltage to the conductive polythiophene composite layer at the bottom of the tile material , monitor the resistance value , when the resistance change rate exceeds 5%, it is marked as the crack occurrence point; S84, using the embedded intelligent monitoring module to record the resistance change trend of the conductive polythiophene composite layer in real time, the intelligent monitoring module sets an alarm mechanism, and records the aging crack growth curve; S85. Apply alternating stress to the tile surface to simulate the dynamic process of crack extension under environmental conditions. Set the alternating stress parameters to a frequency of 5 Hz and an amplitude of 2 MPa. Record the crack extension length after 2 hours of continuous stress to complete crack detection and real-time perception of aging status.
[0026] In this implementation manner, the S84 specifically includes: S841. Based on the initial resistance of the conductive polythiophene composite layer, the relationship between the resistance change rate and the crack extension length during crack extension was measured experimentally to establish a dynamic crack extension model: ; in, represents the real-time resistance of the conductive polythiophene composite layer after crack expansion, represents the initial resistance of the conductive polythiophene composite layer, represents the sensitivity coefficient of crack extension, represents the nonlinear factor of crack growth, Indicates the crack extension length; S842, using a resistance sensor embedded in the bottom layer of the tile material, collecting resistance values and resistance change rates in real time at a sampling frequency of 100 times per second, and combining with timestamp records to form a time series data stream; S843, using support vector machine classification algorithm to perform multi-layer state classification of resistance change rate: ; in, represents the radial basis kernel function, Represents the feature vector Sample points, Represents the feature vector Sample points, represents the exponential function, represents the kernel width parameter; S844, based on Gaussian process regression and improved variational Bayesian inference, crack propagation prediction is performed, a Gaussian process model is established, and a resistance change curve is generated: ; in, represents the probability distribution of the resistance change rate, represents the crack extension length, represents the resistance change caused by crack extension, represents a normal distribution, represents the mean value of the resistance change rate corresponding to crack extension, represents the variance of the resistance change rate corresponding to crack extension; Improved variational Bayesian inference is used to optimize the update of crack extension posterior distribution: ; in, Indicates time The posterior distribution of crack extension length when Indicates time The predicted distribution of the resistance change rate when The crack length in time The prior distribution of ; Output the predicted value of future crack growth length and confidence interval ; S845. Combining the resistance change curve and the predicted crack extension length, the long short-term memory network is used to predict the trend of the crack aging state, and the aging crack extension curve is recorded; S846. According to the crack growth prediction results and trend analysis, the intelligent monitoring module sets three levels of alarm thresholds, including: Level 1 alarm, predicted crack growth in the next 5 hours ; Level 2 alarm, predicted crack growth in the next 3 hours ; Level 3 alarm, predicted crack extension value for the next hour .
[0027] refer to Figure 2 , an anti-corrosion and highly weather-resistant alloy resin tile, consisting of a surface functional layer, an intermediate layer and a bottom layer, specifically including: the surface functional layer is made of a dynamically cross-linked fluorine-silicon-based polymer with a thickness of 50-100 microns, containing vanadium oxide and zinc oxide nanoparticles, and has ultraviolet shielding, self-cleaning and photocatalytic degradation functions; the surface is treated with a fluorinated graphene coating, has super-hydrophobic properties, and the water droplet contact angle is greater than 160°; The middle reinforcement layer is made of nanofiber reinforced composite material with a thickness of 2mm-3mm. It adopts a shell-like layered structure design and has high impact resistance and mechanical properties with a bending modulus greater than 80MPa. The bottom layer is made of a mixture of conductive polythiophene composite materials and flexible fillers, with a thickness of 100-150 microns. It has crack detection and aging status monitoring functions, and performs real-time data analysis and early warning through the embedded intelligent monitoring module; The surface layer, the middle layer and the bottom layer are bonded together by ultrasonic activated bonding technology and are integrally formed by a three-die co-extrusion process. Example 1
[0028] A method for preparing an anti-corrosion and highly weather-resistant alloy resin tile comprises the following steps: (1) Poly(ethylene furandicarboxylate) (PEF), a polyetheramide elastomer toughening agent and an ultraviolet absorber were mixed in a mass ratio of 70:20:10 and melt blended at 240°C to form a matrix material. Modified potassium titanate whiskers with fluorine-containing groups grafted on the surface were added thereto at a weight ratio of 12% of the matrix material, and ultrasonic dispersion technology was used for 25 minutes to uniformly disperse the modified potassium titanate whiskers in the matrix material to obtain a basic composite material.
[0029] (2) Vanadium oxide The composite nanoparticles were prepared by sol-gel method with zinc oxide (ZnO) in a mass ratio of 1:1. The composite nanoparticles were surface-modified with a silane coupling agent and added to the base composite material at a ratio of 5%. The composite material with UV shielding and photocatalytic functions was prepared by stirring at 180°C for 1 hour.
[0030] (3) The composite material was placed in a closed reactor, and a dynamically cross-linked fluorosilicone-based polymer was added at 20% of the total mass of the composite material. At the same time, 0.2% benzoyl peroxide (initiator) and 0.1% hydroquinone (inhibitor) were added, and stirred at 200 rpm for 30 minutes at 140°C. A dynamic stress loading device was connected, and a shear stress of 15 Hz was applied for 2 hours to promote the formation of a cross-linked network of the fluorosilicone-based polymer. After cooling to room temperature, the material was rolled into a sheet with a thickness of 60 microns to obtain a surface functional material.
[0031] (4) The middle reinforcement layer is made of nanofiber reinforced composite material, which is designed and prepared with a shell-like layered structure and has a thickness of 2.5 mm; the bottom conductive material is made of conductive polythiophene composite material and flexible filler mixed in a mass ratio of 9:1, and then thermoformed at 180°C to form a sheet with a thickness of 120 microns. The surface functional material, the middle reinforcement layer and the bottom conductive material are sequentially added to the three-die extruder, and the temperatures of the bottom layer, the middle layer and the surface layer are set to 180°C, 200°C and 220°C respectively. They are extruded synchronously and cooled by a cooling roller to form a multi-layer structure substrate.
[0032] (5) Plasma enhanced chemical vapor deposition (PECVD) is used to deposit a fluorinated graphene coating on the surface of the substrate. The mixed gas is and , the flow ratio was 1:1, the treatment temperature was 120°C, the treatment time was 15 minutes, and a super-hydrophobic surface layer was formed with a surface contact angle of 165°.
[0033] (6) UV aging and salt spray tests were performed on the multi-layer tiles. The UV aging test showed that the color retention rate was 96% after 4000 hours of exposure at 30mW / cm²; there was no obvious corrosion after the salt spray test (5% NaCl, 1000 hours). The photocatalytic performance test showed that the active oxygen concentration of the tiles reached 2000 within 2 hours under 30mW / cm² UV light. Crack detection shows that when the resistance change rate of the underlying conductive composite layer exceeds 5%, the intelligent monitoring module can issue a real-time alarm and successfully predict the aging trend. Example 2
[0034] A method for preparing an anti-corrosion and highly weather-resistant alloy resin tile comprises the following steps: (1) The preparation of the basic composite material is the same as in Example 1.
[0035] (2) The preparation of the composite material with UV shielding and photocatalytic functions is the same as in Example 1, but the amount of composite nanoparticles added is 8% of the mass of the basic composite material.
[0036] (3) The composite material was mixed with the dynamically cross-linked fluorosilicone-based polymer in a mass ratio of 85:15, 0.15% initiator benzoyl peroxide and 0.08% inhibitor hydroquinone were added, and the mixture was stirred at 130°C for 40 minutes. The cross-linking reaction was carried out by dynamic stress at a shear rate of 10 Hz, and the sheet was calendered into a sheet with a thickness of 80 μm after cooling.
[0037] (4) A twin-screw extruder is used to prepare the nanofiber reinforced material of the middle reinforcement layer into a bionic structure sheet with a thickness of 2 mm. A single-screw extruder is used to prepare the bottom conductive material into a sheet with a thickness of 100 μm. Multi-layer tiles are prepared synchronously through three-die extrusion. After cooling, the tiles are subjected to multi-stage rolling treatment to ensure uniform thickness of the sheets.
[0038] (5) PECVD technology was used to deposit a fluorinated graphene coating on the surface of the tile. The treatment time was 12 minutes, forming a superhydrophobic layer with a contact angle of 163°.
[0039] (6) Performance tests show that after high UV (4000 hours) and high salt spray (5% NaCl, 1000 hours) tests, the color retention rate of the tile material reaches 94%, and there is no surface corrosion. Crack detection records the change rate of the bottom layer resistance in real time, and the error in the predicted crack extension length is less than 2%. The final tile material has excellent weather resistance, corrosion resistance and intelligent monitoring capabilities.
[0040] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing corrosion-resistant and highly weather-resistant alloy resin tiles, characterized in that: The steps include: S1, mixing polyethylene furandicarboxylate with a toughening agent and an ultraviolet absorber, forming a matrix material by melt processing, and uniformly adding modified potassium titanate whiskers with fluorine-containing groups grafted on the surface into the matrix material by ultrasonic dispersion technology to prepare a basic composite material; S2. Adding vanadium oxide and zinc oxide composite nanoparticles prepared by a sol-gel method to the basic composite material, and performing surface modification on the composite nanoparticles to prepare a composite material with ultraviolet shielding and photocatalytic functions; S3. Introducing dynamically cross-linked fluorosilicone-based polymers into composite materials with UV shielding and photocatalytic functions, and preparing surface functional materials through dynamic cross-linking technology; S4, preparing and molding the surface functional material, the middle layer nanofiber reinforced composite material and the bottom layer conductive polythiophene-based composite material respectively, and realizing uniform mixing of multiple components and directional arrangement of molecular chains through a dynamic rotating twin-screw extruder to form a multi-layer structure substrate; S5. The surface layer, the middle layer and the bottom layer are co-extruded synchronously by three-die extrusion technology to prepare multi-layer co-extruded tiles; S6. Use ultrasonic activated bonding technology to enhance the interlayer bonding strength of multi-layer co-extruded tiles; S7, depositing a fluorinated graphene nanofilm on the surface of the multi-layer co-extruded tile material using plasma enhanced chemical vapor deposition technology to form a super hydrophobic functional layer; S8. Conduct UV photocatalytic function tests on multi-layer co-extruded tiles to verify the active oxygen generation ability of surface nanoparticles, and complete crack detection and real-time perception of aging status through the conductive polythiophene composite layer embedded in the bottom layer combined with the intelligent monitoring module.
2. The process for preparing a corrosion-resistant and highly weather-resistant alloy resin tile according to claim 1, characterized in that: The S3 specifically includes: S31, placing the prepared composite material with ultraviolet shielding and photocatalytic functions in a reactor, adding a dynamically cross-linked fluorosilicone-based polymer according to 15%-30% of the total mass of the composite material, starting the stirring device of the reactor, raising the temperature to 140° C., controlling the stirring speed to 200 rpm, and maintaining the stirring time for 30 minutes; S32, adding an initiator and an inhibitor during the mixing process, wherein the initiator is benzoyl peroxide, and the amount used is 0.2% of the total mass of the composite material; the inhibitor is hydroquinone, and the amount used is 0.1% of the total mass of the composite material, and continuously stirring to allow the fluorosilicone-based polymer to undergo a preliminary cross-linking reaction; S33, connect the dynamic stress loading device to the reactor, and apply shear rate through the device and shear stress , and set the dynamic stress frequency to 15 Hz, and continue the action for 2 hours to promote the formation of a cross-linked network of fluorosilicone-based polymers; S34, Real-time detection of dynamic mechanical properties of composite materials during dynamic crosslinking, monitoring of storage modulus and loss modulus , calculate the loss factor , control the loss factor range to 0.2-0.4; S35, after the dynamic cross-linking reaction is completed, the cross-linked composite material is slowly cooled to room temperature, and the cooled material is calendered using a calendering device to control the calendering thickness to be 50-80 microns; S36. Conduct surface roughness test on the sheet to ensure that the roughness is less than 0.2 microns. Perform dynamic thermomechanical analysis to test the storage modulus and weather resistance of the material, and conduct UV aging experiments to verify the UV shielding and photocatalytic stability of the surface functional material, and finally obtain the surface functional material.
3. The process for preparing a corrosion-resistant and highly weather-resistant alloy resin tile according to claim 1, characterized in that: The S4 specifically includes: S41, placing the obtained surface functional material in an extruder to prepare a surface functional material, setting the temperature to 180°C-200°C, and setting the screw speed to 60rpm-80rpm, so that the material is fully plasticized and extruded into a uniform sheet, and the thickness is controlled to be 50-100 microns; S42, placing the nanofiber reinforced composite material in a twin-screw extruder to prepare an intermediate layer reinforcement material, adjusting the feed rate to 5-10 kg / h, setting the temperature to 200° C.-220° C., and the screw speed to 100 rpm-150 rpm, adding a continuous fiber reinforcement phase to form a shell-like layered structure, and forming a reinforcement material sheet with a thickness of 2 mm-3 mm by extrusion; S43, mixing the conductive polythiophene composite material and the flexible filler in a mass ratio of 9:1 and placing the mixture in a single screw extruder to prepare a bottom conductive material, setting the temperature to 160° C.-180° C. through a temperature control system, adjusting the screw speed to 50 rpm-70 rpm, and extruding the mixture into a sheet with a thickness of 100-150 μm by a thermoplastic molding process; S44, adding the surface layer functional material, the middle layer reinforcing material and the bottom layer conductive material into the dynamic rotating twin-screw extruder in sequence, adjusting the screw rotation speed to 100rpm-120rpm, setting the feeding order to the bottom layer material, the middle layer material and then the surface layer material, and controlling the temperature gradient to gradually increase from 180°C of the bottom layer to 220°C of the surface layer; S45, cooling the multilayer structure material extruded from the extruder through a cooling roller, setting the cooling roller temperature to 10°C-20°C, adjusting the inter-roller pressure to 1MPa-2MPa, and controlling the sheet thickness through a multi-stage roller cooling system; S46. Finally, a multilayer structure substrate is formed and the cooled multilayer structure material is subjected to a dynamic mechanical property test, and the bending modulus is greater than 80 MPa.
4. The process for preparing a corrosion-resistant and highly weather-resistant alloy resin tile according to claim 1, characterized in that: The S8 specifically includes: S81. Place the multi-layer co-extruded tile material under a UV irradiation device, set the light intensity to 30mW / cm², the irradiation distance to 20cm, and the duration to 2 hours. Determine the active oxygen concentration generated on the tile surface by iodine titration. The active oxygen concentration generated is above; S82. Catalyze the tile surface under ultraviolet light for 1 hour, collect the degraded solution, and measure the transmittance change using an ultraviolet spectrophotometer: ; in, represents the degradation efficiency, represents the initial pollutant concentration, It indicates the concentration of pollutants after degradation; S83, applying a constant voltage to the conductive polythiophene composite layer at the bottom of the tile material , monitor the resistance value , when the resistance change rate exceeds 5%, it is marked as the crack occurrence point; S84, using the embedded intelligent monitoring module to record the resistance change trend of the conductive polythiophene composite layer in real time, the intelligent monitoring module sets an alarm mechanism, and records the aging crack growth curve; S85. Apply alternating stress to the tile surface to simulate the dynamic process of crack extension under environmental conditions. Set the alternating stress parameters to a frequency of 5 Hz and an amplitude of 2 MPa. Record the crack extension length after 2 hours of continuous stress to complete crack detection and real-time perception of aging status.
5. The process for preparing a corrosion-resistant and highly weather-resistant alloy resin tile according to claim 4, characterized in that: The S84 specifically includes: S841. Based on the initial resistance of the conductive polythiophene composite layer, the relationship between the resistance change rate and the crack extension length during crack extension was measured experimentally to establish a dynamic crack extension model: ; in, represents the real-time resistance of the conductive polythiophene composite layer after crack expansion, represents the initial resistance of the conductive polythiophene composite layer, represents the sensitivity coefficient of crack extension, represents the nonlinear factor of crack growth, Indicates the crack extension length; S842, using a resistance sensor embedded in the bottom layer of the tile material, collecting resistance values and resistance change rates in real time at a sampling frequency of 100 times per second, and combining with timestamp records to form a time series data stream; S843, using support vector machine classification algorithm to perform multi-layer state classification of resistance change rate: ; in, represents the radial basis kernel function, Represents the feature vector Sample points, Represents the feature vector Sample points, represents the exponential function, represents the kernel width parameter; S844, based on Gaussian process regression and improved variational Bayesian inference, crack propagation prediction is performed, a Gaussian process model is established, and a resistance change curve is generated: ; in, represents the probability distribution of the resistance change rate, represents the crack extension length, represents the resistance change caused by crack extension, represents a normal distribution, represents the mean value of the resistance change rate corresponding to crack extension, represents the variance of the resistance change rate corresponding to crack extension; Improved variational Bayesian inference is used to optimize the update of crack extension posterior distribution: ; in, Indicates time The posterior distribution of crack extension length when Indicates time The predicted distribution of the resistance change rate when The crack length in time The prior distribution of ; Output the predicted value of future crack growth length and confidence interval ; S845. Combining the resistance change curve and the predicted crack extension length, the long short-term memory network is used to predict the trend of the crack aging state, and the aging crack extension curve is recorded; S846. According to the crack growth prediction results and trend analysis, the intelligent monitoring module sets three levels of alarm thresholds, including: Level 1 alarm, predicted crack growth in the next 5 hours ; Level 2 alarm, predicted crack growth in the next 3 hours ; Level 3 alarm, predicted crack extension value for the next hour .
6. An anti-corrosion and highly weather-resistant alloy resin tile, characterized in that: The alloy resin tile is composed of a surface functional layer, an intermediate layer and a bottom layer, and specifically includes: The surface functional layer is made of dynamically cross-linked fluorine-silicon-based polymer with a thickness of 50-100 microns. It contains vanadium oxide and zinc oxide nanoparticles and has UV shielding, self-cleaning and photocatalytic degradation functions. The surface is treated with fluorinated graphene coating and has super hydrophobic properties, with a water droplet contact angle greater than 160°. The middle reinforcement layer is made of nanofiber reinforced composite material with a thickness of 2mm-3mm. It adopts a shell-like layered structure design and has high impact resistance and mechanical properties with a bending modulus greater than 80MPa. The bottom layer is made of a mixture of conductive polythiophene composite materials and flexible fillers, with a thickness of 100-150 microns. It has crack detection and aging status monitoring functions, and performs real-time data analysis and early warning through the embedded intelligent monitoring module; The surface layer, the middle layer and the bottom layer are bonded together by ultrasonic activated bonding technology and are integrally formed by a three-die co-extrusion process.
Citation Information
Patent Citations
Long-acting and weather-proof resin tile co-extrusion material with light screening function and preparation method thereof
CN110079043A
High-weather-resistance hollow resin tile and manufacturing process thereof
CN110408168A
High performance coatings for building panels
CN113248957A